TRANSFORMASI MEDIA TIKTOK SEBAGAI RUANG BARU JURNALISTIK ADAPTASI MEDIA TRADISIONAL TERHADAP TREN DIGITAL - Saragih, M Yoserizal (eScience Humanity Journal, 2024)
This article discusses the transformation of TikTok from the entertainment platform into a new journalistic space, while exploring how traditional media adapts to digital trends. With interactive short video formats, TikTok has opened opportunities for journalists to reach younger audiences. However, the platform also presents the challenges associated with validity, credibility, and news presentations that match the ethics of the journalistic ethics. Through a qualitative approach, this article examines the role of TikTok as the distribution media of information and adaptation carried out by traditional media to remain relevant in the digital age